Potential Interactions between miRNAs and Hypoxia: A New Layer in Cancer Hypoxia - Tapeh, Behnam Emamgolizadeh-Gurt; Alivand, Mohammad R.; Solalii, Saeed (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Hypoxia pathway and aberrant miRNA expression profile play crucial roles in the development of various cancers. Recent studies have emphasized that there are many collaborations in this cases because both of them are involved in cancer cell processes, including differentiation, metastasis, and cell proliferation and signaling pathways. Further studies have elucidated that miRNAs affect the hypoxia route, and more interestingly, the hypoxia pathway also affects miRNAs expression profile. The literature review summarizes the fundamental roles of hypoxia-related miRNAs in different cancers. The mutual interactions between miRNAs and hypoxia are a new layer of complexity in cancer hypoxia, which might be helpful in controlling cancer progression. It is also possible that the hypoxia pathway is initiated by miRNAs. In contrast, the hypoxia pathway regulates the expression of a large group of miRNAs. In this review for the first time, we discussed the significant interactions between hypoxia and miRNAs in order to determine new perspectives for new therapeutic aims in the field of cancer.
Keywords: HIF1 alpha